2015
DOI: 10.1007/s13197-015-2147-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of technical cashew nut shell liquid on thermally-induced trans isomers in edible oils

Abstract: The effects of technical cashew nut shell liquid (TCNSL) on the trans isomerization of edible oils during heating are investigated. Edible oils were subjected to thermal treatment at various heating times and temperatures. Our results show that the addition of TCNSL to edible oils at the appropriate concentration during heating suppresses trans fatty acid formation and induces formation of conjugated linoleic acid (CLA) isomers. A concentration of 0.2 % TCNSL demonstrates the best ability to inhibit formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…() showed that when using a cyanopropyl siloxane column, the retention times of some TLNA methyl esters, such as 9 E ,12 E ,15 Z and 9 E ,12 Z ,15 E , are so similar that they appear as a single peak and must be expressed as the sum of the two compounds. These two isomers could not be separated by other studies using cyanopropyl siloxane columns (Hou et al ., ; Inagaki & Numata, ; Guo et al ., ,b). However, our analysis showed that of the two isomers mentioned above, only the 9 E ,12 Z ,15 E isomer was detected in trilinolenin heated to temperatures below 240 °C.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…() showed that when using a cyanopropyl siloxane column, the retention times of some TLNA methyl esters, such as 9 E ,12 E ,15 Z and 9 E ,12 Z ,15 E , are so similar that they appear as a single peak and must be expressed as the sum of the two compounds. These two isomers could not be separated by other studies using cyanopropyl siloxane columns (Hou et al ., ; Inagaki & Numata, ; Guo et al ., ,b). However, our analysis showed that of the two isomers mentioned above, only the 9 E ,12 Z ,15 E isomer was detected in trilinolenin heated to temperatures below 240 °C.…”
Section: Resultsmentioning
confidence: 97%
“…Our results also showed that the addition of additives to inhibit the formation of 9 E ,12 Z ,15 Z , 9 Z ,12 Z ,15 E and 9 Z ,12 E ,15 Z isomers may be an optional way to reduce TLNA isomers without the need for reducing the heating temperature or reaction time. Previous studies showed that the formation of trans fatty acid heating at the same temperature or time can be significantly inhibited by the additives (Guo et al ., , ), which is also confirmed our results to a certain extent.…”
Section: Z12z15z Isomerisation Reaction Kineticsmentioning
confidence: 97%
“…GC has been the preferred method for such analyses because of its accuracy and relatively low cost . However, GC equipped with routine cyanopropyl siloxane phase capillary columns, such as the popular SP‐2560 or SP‐2340 (Sigma‐Aldrich), CP‐Sil 88 or HP‐88 (Agilent) or BPX70 (SGE Analytical Science) columns, is unable to completely separate cis / trans ‐ALAs in edible oils, resulting in some overlap of geometrical and positional isomers . In recent years, several improved GC methods have been developed using these columns with optimized run conditions, but even though the analysis time is 3–10 times shorter than that of conventional GC, the separation of TALAs can rarely be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported that trans isomerization of trilinolein could be achieved at high temperatures, producing 9 t ,12 t , 9 c ,12 t and 9 t ,12 c isomers as the predominant products . Recent studies have provided insight into the chemistry of CFAs formed from heated trilinolein . However, the identities and concentrations of the c , t , trans,cis ( t , c ) and t , t isomers of conjugated linoleic acids formed from glycerides have not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…Trilinolein and trilinoelaidin are glyceride molecules of linoleic acid (C18: 2,9,12) containing only cis,cis (c,c) and trans,trans (t,t) configurations, respectively. The heat-induced products from these molecules should originate from the acid molecules in the glyceride backbone.…”
Section: Introductionmentioning
confidence: 99%